Education, Physical Activity, and Reproductive Health in Women: Understanding the Impact of the Vaginal Microbiome - Borychowska, Emilia; Czudowska, Michalina; Zawadzka, Magdalena; Marszałek, Dominika; Kurzątkowska, Klaudia; Bystros, Aleksandra Natalia; Drozdowska, Marta; Ocimek, Aleksandra; Gwóźdź, Karolina; Mierzejewska, Zofia Aneta (Quality in Sport, 2026)
Background. The vaginal microbiome is essential for women’s reproductive health, affecting fertility, implantation, pregnancy outcomes, and vulnerability to gynecological conditions. It is increasingly recognized within the broader context of women’s health literacy and lifestyle, including physical activity, which may influence microbial balance. Aim. To summarize current evidence on the composition and clinical importance of the vaginal microbiome while integrating insights from public health, health education, and sports science. Material and methods. A review of open access studies published between 2021 and 2025 identified 23 eligible articles. Additional literature on women’s health education and physical activity was included to highlight interdisciplinary links. Results. Lactobacillus-dominant communities, especially those enriched with Lactobacillus crispatus, support mucosal stability and favorable reproductive outcomes. Dysbiosis, characterized by low Lactobacillus levels and high microbial diversity (CST IV), is linked to bacterial vaginosis, subfertility, implantation failure, and preterm birth. Education and lifestyle-focused interventions may help mitigate dysbiosis, while early evidence suggests physical activity supports systemic regulation relevant to microbial stability. Conclusions. The vaginal microbiome significantly influences reproductive and overall health. Integrating microbiome knowledge into health education and lifestyle promotion may improve preventive strategies and clinical outcomes.